SUN-157 Delayed Diagnosis of Cushings Syndrome: Hiding in Plain Sight! - Jalil, Fatima (J Endocr Soc, 2020)
BACKGROUND: Endogenous Cushing’s syndrome (CS) is rare, with an incidence of 0.7-2.4/million people/year.(1) It should be considered in individuals with diabetes (DM), hypertension (HTN), osteoporosis or electrolyte abnormalities.(2) We present a patient with DM2 and persistent hypokalemia for 10 years found to have ACTH-independent Cushing’s disease as the cause of metabolic syndrome. Case: 62 y.o. M admitted with abdominal pain, a history of DM2 (2012) on Metformin 500 mg BID, HTN (2010) and on ramipril 10 mg qd, with chronic lymphedema on furosemide 20 mg qd. He reported 3-inch height loss. On exam, had facial plethora, moon facies, supraclavicular fullness, thick violaceous abdominal striae and kyphosis. Past history was significant for abdominal/leg cellulitis, muscle weakness, difficult to heal wounds, easy bruising and recurrent hospitalizations for hypokalemia, despite being on KCl up to 80 mEq/d for 10 years. Labs showed AM cortisol at 22.6 ug/dL, ACTH <5 pg/mL, 24-hour urine free cortisol of 523 ug/d (normal < 60 ug/d). AM cortisol after 1 mg overnight dexamethasone suppression was 36.8 g/dL, ACTH <5 pg/mL. CT abdomen showed right adrenal nodule, 4.0 x 3.5 cm with density of 22 HU. MRI showed lipid-poor adenoma measuring 3.9 x 3.5 cm, raising concern for adrenocortical malignancy. Patient underwent right adrenalectomy. Pathology was consistent with benign adenoma showing no nuclear pleomorphism, lipid rich cells containing eosnophillic cytoplasm. Mib-1 stain <1% cells and positive inhibin. He was maintained on steroids post op due to concern about adrenal insufficiency. Hypokalemia, DM and lymphedema resolved completely 4 months post op with weight loss of ~30 pounds. HbA1c improved to 5.1%, metformin was stopped and he was maintained on Carvedilol 6.125 mg BID for HTN. He was diagnosed with osteoporosis with T score -4.0 at mean femoral neck, -2.9 for mean total hip with non-diagnostic spine. He had multi-level chronic compression fractures of the mid-thoracic spine. Conclusion: Delayed diagnosis of CS, as occurred in our patient, can result in detrimental consequences such as life threatening electrolyte abnormalities, cardiovascular events, fractures and premature death.(1) Identifying CS can be challenging as clinical presentation is variable. (2,3) Early recognition, diagnosis and control of CS is crucial to decrease morbidity and mortality. Our patient demonstrated rapid resolution of DM, hypokalemia and lymphedema after surgery; however, prolonged exposure to endogenous cortisol resulted in compression fractures and osteoporosis requiring follow up treatment. References: 1. Ille I et al, The Multifarious Cushings. Acta Endocrinol.2019 15(2):261-269 2. Reimondo G et al, Lab differentiation of Cushings syndrome. Clin Chim Acta. 2008;388(1-2):5-14 3. Fan L et al, Association of hypokalemia with cortisol and ACTH levels in Cushings disease. Ann N Y Acad Sci. 2019